Older than dirt : a kinda-sorta biography of Earth - Brown, Don, 1949-; Perfit, Michael R., 1949- (Houghton Mifflin Harcourt, 2017)
Presents a brief biography of Earth's formation using a graphic-novel format and an illustrated talking beaver to walk the reader through billions of years of history.